CAPITAL ASSETS MANAGEMENT OF PAKISTAN COMPANIES - Bunyod Usmonov (Scholar Express Journals, 2024)
The current study investigates the effect of working capital management on a company's performance, taking into account the moderating role of ownership structure. Utilizing a fixed-effect model, the research found a notable negative relationship between leverage, average collection period, and quick ratio with firm performance, while current ratio, accounts payable, and inventory turnover positively influenced performance. Therefore, it is suggested that owners and managers optimize their resource management to improve profitability. Furthermore, investors and shareholders are advised to consider the extent of institutional and managerial ownership when making investment choices.
Keywords: quick ratio; working capital